Papers of Donald Stuart - Stuart, Donald, 1913-1983. (1942)
Personal correspondence. Correspondence with publishing houses and re Commonwealth Literary Fund awards. Handwritten drafts of short stories and a novel. Typescript broadcasts. Newspaper clippings. Photographs.
Manuscript reference no. : MS 3156.
Digital master available
Donald R. Stuart, writer and broadcaster, born 1913 in Western Australia. Published "Yandy", 1969, "The driver", 1961, "Yaralie", 1962 and "Ilbarana", 1971.
Descriptive list (1 p.) available.
Keywords: Stuart, Donald, -- 1913-1983 -- Archives; Commonwealth Literary Fund; Authors, Australian -- Archives; Authors